Implementasi Kriptografi Dengan Algoritma RSA pada Aplikasi Transfer File - Wahyu Widodo; Racmad Ardiyanto; Rinci Kembang Hapsari (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2023)
Currently, the security of information on data has become an important role in the world of technology, especially in exchanging information. One of them is file transfer. Transferring files here requires an internet connection, which will likely spread the news to irresponsible parties. Therefore, cryptography is used to secure information using the RSA algorithm. From the implementation of cryptography with the RS algorithm, there are three processes: key generation, encryption, and decryption. The results of this study from the RSA algorithm computation time for encryption for testing files with different numbers of characters have an average of 825 ms. In comparison, decryption is 781.2 ms with Throughput, which averages 221,470 Kbps.